Enhancing Nasal Tip Control: The Role of Septum Anchorage Sutures in Modern Rhinoplasty - Espinosa-Reyes, Jorge A.; Ochoa-Álvarez, Juan C.; García, Rodrigo F. F. P. (Facial Plastic Surgery, 2026)
The septocolumellar suture technique has shown consistent efficacy in achieving precise nasal tip aesthetics for over 20 years. This study aims to evaluate the long-term outcomes of primary endonasal rhinoplasty.Retrospectively analyze 1,096 consecutive patients who underwent primary endonasal rhinoplasty using the septocolumellar suture technique between March 2005 and March 2025. The procedure anchors the medial crura to the caudal septum at variable distances from the anterior nasal spine, allowing control of tip projection and rotation. Objective and photographic analyses assessed the nasal tip parameters, including projection, rotation, shape, deviation, alar width, and flare. Statistical significance was set at p < 0.001.Long-term stability of nasal tip projection and rotation was maintained in 96% of the patients at a minimum 12-month follow-up. All the evaluated parameters demonstrated statistically significant improvement (p < 0.001). The revision and complication rates were 3.2 and <1%, respectively.The septocolumellar suture technique is a reliable and minimally invasive method for nasal tip refinement in rhinoplasty. It ensures stable aesthetic outcomes while preserving nasal support and functional integrity. This technique effectively enhances tip projection in mestizo patients using intrinsic anatomy and can be applied in both open and closed approaches.
Keywords: septocolumelar suture; nasal tip positioning; nasal tip preservation; rhinoplasty; medial crura; caudal septum; nasal tip projection